The Settlement of Electronic Commerce Transactions Through Online Dispute Resolution Mediation (ODR) in Indonesia - Anis Rifai (Activa Yuris: Jurnal Hukum, 2022)
Nowdays, the internet has become a vital necessity in the daily life of  people over the world. Once the internet is publicly opened, the internet was used also to benefit trade. At this moment, it is easy to find out plenty of common modern trade transactions that use technology as a medium,  which is commonly known as electronic transactions or electronic commerce (e-commerce). A challenge of the changing era that needs serious attention is how to use the internet safely without getting into trouble because of  the unpreparedness of Indonesia in various aspects (mainly in legal aspect) in order to anticipate all of the possible occurence relating to the electronic trading system. The problem is usually resolved through the courts and alternative dispute resolution. The problems that occurred at this time encompassing the justice seekers (in this case society) who are suffering a loss as a result of e-commerce transactions which is blocked by a considerable distance between the buyer with merchant. E-commerce and judicial process at court also takes up a long time and requires sophisticated mechanism. In connection with this, this paper will outline the settlement of e-commerce by implementing a mediation via online dispute resolution (ODR) for dispute resolution electronic commerce transactions in Indonesia